Adhesions as an uncommon complication of k-wiring in paediatric phalangeal fractures - Nanchappan S; Parminder GS; Nur Azuatul AK; Tan, JA; Ahmad Suparno B; Jamari S; Shalimar Abdullah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Paediatric hand fractures are common and prompt management is mandatory to achieve a good functional outcome. However many fail to realize that treating a fracture does not only involve bones but the soft tissues, as well. K-wiring itself can be difficult with multiple attempts inadvertently injuring the flexor or extensor tendons and resulting in adhesions. We highlight this possible complication of K-wiring which we believe is under reported due to the perception that K-wiring is a simple procedure. We present a case of a 9-year-old child, who sustained a closed displaced fracture of the base of the proximal phalanx (Salter Harris type 2) of the left index finger. He underwent percutaneous K-wiring but was complicated with severe adhesions of the flexor digitorum profundus (FDP) and flexor digitorum superficialis tendons (FDS). He was unable to flex the proximal and distal interphalangeal joints of the affected finger. We subsequently performed tendon adhesiolysis twice together with A2 pulley reconstruction, to restore movement of the finger. K-wiring of the fingers are not just simple bony procedures but also involve soft tissue components which can be prone to adhesions.